Solution For The Development Of Prisoners In Class III Gorontalo Women's Prison - Sumiyati Beddu; Darmawati Darmawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The correctional facility is an implementing agency of the criminal system that has a function to foster citizens of correctional development, including in this case women undergoing an obligatory sentence to participate in a whole series of coaching activities in the correctional institution. This paper aims to look at the implementation of this form of guidance and find the right solution related to the problem of guiding prisoners in women's prisons, especially Class III Gorontalo prisons. The results obtained were that the implementation of the existing forms of guidance at the Class III Gorontalo Women's Prison was divided into three stages of coaching, namely the initial stage, the advanced stage and the final stage coaching. To overcome problems in the implementation of coaching women prisoners, synergy is needed between all parties involved, starting from prisoners, correctional officers and related agencies to cooperate with each other in the implementation of training for female prisoners. For this reason, it is necessary to repair and add infrastructure to support coaching activities and to involve officers in prisons through training activities that can support the implementation of coaching. Concerning the handicrafts of prisoners, it is also expected to increase marketing through the media, given the condition of Covid 19 which limits people from being able to interact directly with prisoners in prison